ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI EFEKTIFITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI KABUPATEN SIDENRENG RAPPANG - Erfina Erfina; Muh. Arisal Asad (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
Tax is one of national development funds in order to improve the welfare of society. In this regard the importance of the tax management is a priority for the government. In connection with the land and building tax revenue gained by the region, as many looks are still many deficiencies in it, especially the low participation in the payment of property tax that it was his duty. And the most obvious kejangggalan happens on the ground is often the village chief / headman pay off their own property taxes by using private money or cash villages. Thus the required analysis of the factors that influence the effectiveness of property tax collection. This study aimed to analyze the effectiveness of property tax collection and the factors that influence it. This type of research is quantitative descriptive. The sampling technique is purposive, where the total sample of 72 respondents. Data collection techniques, using questionnaires for primary data. Technique of data analysis, with quantitative descriptive analysis approach. The results of this study show that the effectiveness of the UN voting in Sidrap in general it can be concluded that proved effective operation of the processed questionnaire data obtained in which the amount of 74.54%. which means in the category efektif.Faktor which affect three types ie: Environmental characteristics with the yield at 68.1% Less influential, Full Feature with a yield of 72.5% Less influential, Policy and Practice Management with a yield of 68.92% Less take effect. Results of statistical processing to test R Square: 0,025 x 100% = 2.5 (the effect of X to Y) were 100% - 2.5% = 97.5% (the rest is influenced by other factors). This means that the effect of x only by 2.5%.